Penyuluhan dan Demonstrasi Cuci Tangan Pakai Sabun (CTPS) dan Sikat Gigi di SD Kampung Simporo Kabupaten Jayapura - Irjayanti, Apriyana; Tambing, Yane; Bela, Sarni Rante Allo; Irmanto, Maxsi; Rumaropen, Nofa Falentina (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Clean and Healthy Living Behavior at school is a behavior that is practiced by students, teachers, and the whole community in the school environment, based on awareness that allows individuals to independently improve health, prevent disease and play an active role in creating a healthy environment. This counseling and demonstration service activity aims to increase students' knowledge about the importance of clean and healthy living behavior in the school environment in order to create a healthy school. The community service was carried out on Friday, 19 August 2022 at Kampung Simporo Elementary School, Jayapura with a total of 39 elementary school students, using counseling methods and demonstrating how to wash hands with soap and brush their teeth accompanied by a discussion and question and answer session after finished presenting short material and playing an animated video. The form of evaluating the success of this activity is by direct observation of students in practicing how to wash their hands with soap and brush their teeth whether they are in accordance with the steps conveyed during counseling. The results show that all students are able to apply the material that has been delivered, seen during the demonstration activities they can practice it well at each stage. It is hoped that with this activity students, teachers, and the community around the school will be able to improve health and prevent disease and play an active role in creating a healthy environment.